Evaluation of anti-inflammatory properties on the surface of dental implants depending on the type of processing (Part 1) - S. D. Varzhapetian; M. A. Shyshkin; T. V. Strogonova (Patologìâ)
The aim. To study of the anti-inflammatory properties of the surface of commercial dental implants with different processing methods using the example of the course of the first stage of implantation.